Assessment of Financial Reforms and their Impact on Economic Growth in Syria in the Third Millennium - case study (Latakia University Journal - Economic and Legal Sciences Series, 2023)
With the beginning of the third millennium, Syria took important steps towards the policies of openness and liberalization, as the first decade witnessed many reforms in this regard. On the financial level, the government announced for the first time financial reforms focused on the banking sector and the establishment of the stock market. On the commercial level, trade liberalization has been carried out with many countries. On the level of financial information, Syria has adopted the IFRS in order to achieve international consensus on the financial reports level. However, these steps quickly faltered after the outbreak of the Syrian crisis in 2011, which inflicted heavy losses on the economy and stock markets and reduced the financial sector size. This research aims to evaluate the implemented financial reforms, and to do this it was necessary before to analyze the contemporary Syrian financial system and identify the problems that required these reforms. Many economists agree that the main problem of the Syrian economy lies in the financial system, more precisely in the issue of financing this economy and in the financial policies followed. The analysis of the contemporary history of the Syrian economy indicates that the latter was based, for long period, on the direct interventionist policies and the central planning model. The government found in the policies of directing credit and managing interest rates an important factor for production. In order to finance the budget debt and maintain a low inflation rate, it excluded private sector from competition for the funding available in the banking sector. To control the banking system, it reduced it to a large commercial bank and four small specialized banks. To encourage national industry, it restricted imports and implemented a multiple parities of exchange regime. The analysis of the Syrian financial system showed that it fits with the state of “financial repression” defined by the authors of the “Financial Liberalization Theory”, which leads to undermining the financial system’s contribution to financing the economy, Syria is considered one of the most weak level of financial development in the MENA countries. The research concludes that these reforms were not sufficient to solve the chronic problems caused by a large legacy of the central economy and financial repression. Moreover, the reforms approach was inappropriate to improve the banking sector efficiency, in addition to they were suffering from bad timing and the absence of a comprehensive strategy that includes adherence to the reform stages. The study also came out with recommendations, of which the most important is the need to prepare an appropriate background before initiating any financial reform, meaning the necessity of improving the quality of the prevailing initial conditions such economic, financial, institutional, legal, legislative and judicial conditions and the quality of information, because the starting conditions quality was the reason behind the success of some developing countries and the failure of others in reforming their financial systems. By realizing that the ideological transition towards market economy is not just a promulgation of institutional laws, a transitional stage must be considered during which appropriate monetary and financial controls are put in place to abandon interventionist policies and establish the institutional structure of the banking system that secures this passage.